Modeling and Exploration of the Voltage-Controlled Magnetic Anisotropy Effect for the Next-Generation Low-Power and High-Speed MRAM Applications - Kang, Wang; Ran, Yi; Zhang, Youguang; Lv, Weifeng; Zhao, Weisheng (IEEE transactions on nanotechnology, 2017)
Spin transfer torque magnetic random access memory (STT-MRAM) has been widely regarded as a potential nonvolatile memory candidate in the next-generation computer architectures. Nevertheless, the write energy consumption and delay are two significant concerns for STT-MRAM, blocking its applications for working memories. Recently, magnetic tunnel junction (MTJ) based on voltage-controlled magnetic anisotropy (VCMA) effect shows tremendous superiority in terms of dynamic write energy and delay over the STT-based one, attracting much attention for advanced low-power and high-speed MRAM designs. In this paper, we evaluate the prospects and challenges of the VCMA-MTJ devices for advanced MRAM applications. First, the magnetization dynamics of the free layer of VCMA-MTJ devices are studied by solving a modified Landau-Lifshitz-Gilbert equation. Afterward, a VCMA-MTJ electrical model is built by integrating the VCMA effect, Slonczewski STT model, Brinkman resistance model, and tunnel magnetoresistance model. Finally, three MTJ switching strategies, including precessional VCMA, STT-assisted precessional VCMA and STT-assisted thermally-activated VCMA, are studied for MRAM applications. Our results show that the STT-assisted precessional VCMA strategy is the most potential one for high-speed and low-power VCMA-MRAM design. This paper provides models, strategies, and guidelines for VCMA-MRAM design and application.